Secretários dos amantes: arquegeneparatextomediatradulogia do sabor no romance epistolar Cartas Portuguesas - Lima, Carlos Adriano Ferreira de (2012)
This is the result of a research which concerns to literary tranlations of the Portuguese Nun, understood as a Epistolary Romance. It is structured in five letters with loving theme, it has been written in first person, in an effort to female utterance, in the character and sender a nun to her lover, a French nobleman, who seems to disregard the missives. Offshoots of these epistles have created versions, answeres, denials and assignments of authenticity to the characters that has shaped in people who lived in the epoch of the first release in French in XVII and it has been reinforced in the following centuries. Along the course of this research, we noticed an in-disciplinary dialogue to which we have resorted to the term arquegeneparatextomediatradulogia,it is a neologism aims to present the main theorical and methodological choices to expound the work. The main character dwells in many translations and various semiosis such as dramatics, cinema, poetry, romance. It tramutes itself in many possible Marianas, but it just interest us, among many of them, Who were created in the folds and unfolds into the Portuguese language, whether by their paratextuals items in the prefaces and other elements of meaning that accompany, surround and involve the letters, as well as the wrinkles made up by the literary translations and publications by different editorial projects, translators and also considered as "refunds" to the "native” language, which would be the Portuguese. For the majority of the readers, the first contact with the academic text production is its abstract and, depending on the circumstances, the only one. It is a love story that gone wrong, in the fictional plot, or in real life, but which found enjoyment as literary work and its successive translations, it became a national Portuguese symbol, literary canon and target of the dispute by the nationality of the work and authorship. Here is a work that purposes to confer flavor to the discussions about the epistolary romance Portuguese nun and intending to highlight translations as an of literary history. Bon appétit.